On Solvability of Third-Order Operator Differential Equation with Parabolic Principal Part in Weighted Space - Araz R. Aliev; Sabir S. Mirzoev; Mustafa A. Soylemezo (Journal of Function Spaces)
Sufficient conditions are found for the correct and unique solvability of a class of third-order parabolic operator differential equations, whose principal parts have multiple characteristics, in a Sobolev-type space with exponential weight. The estimates for the norms of intermediate derivative operators are obtained and the relationship between these estimates and solvability conditions is established. Besides, the connection is found between the order of exponential weight and the lower bound for the spectrum of abstract operator appearing in the principal part of the equation.